Rituals of royalty and the elaboration of ceremony in Oman: View from the edge - Chatty, D (Cambridge University Press, 2009)
Ceremony and elaborate protocols are commonly associated with kingship, authority, and power. The pageantry associated with the British monarchy in its public ceremonials, for example, is imbued with a sense of an ancient past. Yet, these traditions are recent inventions derived from the late Victorian period. Traditions, particularly Western practices, are often made up, choreographed, and then formally instituted in a matter of a few years, rapidly gaining a sense of permanence. Sometimes entirely new symbols and devices are invented to confirm gravitas and substance and to serve as rallying points for the new entity (e.g., Marianne, John Bull, or Uncle Sam). © 2009 Cambridge University Press.